Reprogramming fibroblasts and peripheral blood cells from a C9ORF72 patient: A proof‐of‐principle study. Issue 7 (3rd March 2020) - Bardelli, Donatella; Sassone, Francesca; Colombrita, Claudia; Volpe, Clara; Gumina, Valentina; Peverelli, Silvia; Catusi, Ilaria; Ratti, Antonia; Silani, Vincenzo; Bossolasco, Patrizia
Abstract: As for the majority of neurodegenerative diseases, pathological mechanisms of amyotrophic lateral sclerosis (ALS) have been challenging to study due to the difficult access to alive patients' cells. Induced pluripotent stem cells (iPSCs) offer a useful in vitro system for modelling human diseases. iPSCs can be theoretically obtained by reprogramming any somatic tissue although fibroblasts (FB) remain the most used cells. However, reprogramming peripheral blood cells (PB) may offer significant advantages. In order to investigate whether the choice of starting cells may affect reprogramming and motor neuron (MNs) differentiation potential, we used both FB and PB from a same C9ORF72 ‐mutated ALS patient to obtain iPSCs and compared several hallmarks of the pathology. We found that both iPSCs and MNs derived from the two tissues showed identical properties and features and can therefore be used interchangeably, giving the opportunity to easily obtain iPSCs from a more manageable source of cells, such as PB.